Association between delivery of a small‐for‐gestational‐age neonate and long‐term maternal cardiovascular morbidity☆. Issue 1 (13th July 2013) - Pariente, Gali; Sheiner, Eyal; Kessous, Roy; Michael, Sherf; Shoham‐Vardi, Ilana
Abstract: Objective: To investigate whether delivering a small‐for‐gestational‐age (SGA) newborn is a risk factor for subsequent long‐term maternal cardiovascular morbidity. Methods: Data were analyzed from consecutive pregnant women who delivered at Soroka University Medical Center, Beer‐Sheva, Israel, between 1988 and 1999, and were followed‐up retrospectively until 2010. Long‐term cardiovascular morbidity was compared among women with and without SGA neonates. Results: During the study period, 47 612 deliveries met the inclusion criteria, and 4411 (9.3%) women delivered an SGA neonate. Delivery of an SGA neonate was a risk factor for long‐term complex cardiovascular events, including congestive heart failure, hypertensive heart and kidney disease, and acute cor pulmonale (odds ratio [OR], 2.3; 95% confidence interval [CI], 1.3–4.4; P = 0.006); and long‐term cardiovascular mortality (OR, 3.4; 95% CI, 1.5–7.6; P = 0.006). Women who delivered an SGA neonate had a significantly higher risk for cardiovascular mortality during the follow‐up period (Kaplan–Meier survival analysis, P = 0.002). Delivery of an SGA neonate remained an independent risk factor for long‐term maternal cardiovascular mortality (Cox multivariable regression: adjusted hazard ratio, 3.5; 95% CI, 1.5–8.2; P = 0.004). Conclusion: Delivery of an SGA neonate is an independent risk factor for long‐term cardiovascular morbidity in a follow‐up period of more than 10 years.